The potential mechanism of Fructus Ligustri Lucidi promoting osteogenetic differentiation of bone marrow mesenchymal stem cells based on network pharmacology, molecular docking and experimental identification. Issue 4 (1st April 2022) - Kong, Yuanhang; Ma, Xinnan; Zhang, Xin; Wu, Leilei; Chen, Dechun; Su, Bo; Liu, Daqian; Wang, Xintao
ABSTRACT: Recent studies have shown that the differentiation of bone marrow mesenchymal stem cells (BMSCs) into osteogenic lineages can promotes bone formation and maintains bone homeostasis, which has become a promising therapeutic strategy for skeletal diseases such as osteoporosis. Fructus Ligustri Lucidi (FLL) has been widely used for the treatment of osteoporosis and other orthopedic diseases for thousands of years. However, whether FLL plays an anti-osteoporosis role in promoting the osteogenic differentiation of BMSCs, as well as its active components, targets, and specific molecular mechanisms, has not been fully elucidated. First, we obtained 13 active ingredients of FLL from the Traditional Chinese Medicine Systems Pharmacology (TCSMP) database, and four active ingredients without any target were excluded. Subsequently, 102 common drug-disease targets were subjected to protein-protein interaction (PPI) analysis, Gene Oncology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. The results of the three analyses were highly consistent, indicating that FLL promoted the osteogenic differentiation of BMSCs by activating the PI3K/AKT signaling pathway. Finally, we validated previous predictions using in vitro experiments, such as alkaline phosphatase (ALP) staining, alizarin red staining (ARS), and western blot analysis of osteogenic-related proteins. The organic combination of network pharmacological predictions with in vitro experimental validation comprehensively confirmed the reliability of FLL in promoting osteogenic differentiation of BMSCs. This study provides a strong theoretical support for the specific molecular mechanism and clinical application of FLL in the treatment of bone formation deficiency. GRAPHICAL ABSTRACT: uf0001